The principles of shariah-compliant negotiation (SCN) from the Islamic organization perspective - Ramdani, Abbas; Mohammed, Rosli; Ahmad, Mohd Khairie (Medwell Journals, 2016)
The major symbol of the twenty-first century is the emergence of the Islamic system of management which has remarkable increase among Islamic organizations.A number of organizations have adopted the Islamic system of management to manage their organizations.This was a result of the need to align with the Shari’ah system.However those Islamic organizations negotiate and deal with each other and with others in order to satisfy their interest and meet their objectives.It is therefore important to know the Shariah principles which they execute in their negotiation with their various customers.Therefore the purpose of this study is to bring out the Shariah-complaint negotiation principles from the Islamic organization point of view.A series of interviews were conducted with four expertise groups to drive data of this study.A set of thematic data analysis was directed by the assistance of the NVIVO 8 software to develop the principles themes and sub-themes.Finding identified that Islam as a complete way of life has set several principles, Muslims must observe and in their negotiation practices.Thus, the Islamic organization must conduct their negotiations within the Shariah teachings to fulfill their objectives and get the spiritual satisfaction.